Sie sind auf Seite 1von 10

# 17-02-14

Activities

1
1

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 1
Determine the Fourier transform of the impulse signal δ(t).

2
2

1
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 1 Solution
Determine the Fourier transform of the impulse signal δ(t) :
∞ ∞
X (ω ) = ∫ x (t ) e− jωt dt = ∫ δ (t ) e− jωt dt = 1
−∞ −∞

F {δ (t )} = 1

3
3

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 2
Determine the Fourier transform of the decaying exponential
x(t),

x(t ) = e − at u(t )

4
4

2
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 2 solution
x (t ) = e−at u (t )
∞ ∞ ∞
X (ω ) = ∫ x (t ) e− jωt dt = ∫ e−at u(t)e− jωt dt = ∫e −(a+ jω )t
dt
−∞ −∞ 0

1 ⎡ −(a+ jω )t ⎤∞ 1
=− ⎣e ⎦0 =
a + jω a + jω
1 1
X (ω ) = =
a + jω a +ω2
2

1 ⎛ω ⎞
∠X (ω ) = ∠ = ∠1− ∠(a + jω ) = − tan −1 ⎜ ⎟
a + jω ⎝a⎠

1
F {e−at u (t )} =
a + jω 5
5

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 3
Determine the aperiodic signal g(t) if the Fourier transform
of g(t) is given by G(ω) = δ(ω).

6
6

3
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 3 solution
Since the Fourier transform of g(t) is known, we apply
inverse Fourier transform,
∞ ∞
1 1 1
g (t ) =

∫ G (ω ) e jωt dω = 2π
∫ δ (ω ) e jω t
dω =

−∞ −∞

7
7

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 4
Determine the signal x(t) if the Fourier transform is a
frequency-shifted impulse function X(ω) = δ(ω – ω0).

8
8

4
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 4 solution
Since the Fourier transform of the signal is given, we apply
inverse Fourier transform:
∞ ∞
1 jω t 1 jω t 1 jω0t
g (t ) =

∫ G(ω )e dω =

∫ δ (ω − ω ) e 0 dω =

e
−∞ −∞

9
9

## Activity 5 Table Look-up Method

Using the look-up table method, calculate the inverse CTFT of
the following function:
2 ( jω ) + 24
X (ω ) =
( jω )2 + 4( jω ) + 29

10
10

5
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 5 solution
The function can decompose into simpler terms, whose
inverse CTFT can be determined directly from Table 5.2
2 ( jω ) + 24 2(2 + jω ) + 20
X (ω ) = =
( jω ) + 4( jω ) + 29 (2 + jω )2 + 52
2

2(2 + jω ) 4*5
= +
(2 + jω ) + 5 (2 + jω )2 + 52
2 2

## From Table 5.2,

a + jω
e−at cos(ω 0 t)u(t) ↔
(a + jω )2 + ω 02
ω0
e−at sin(ω 0 t)u(t) ↔
(a + jω )2 + ω 02 11
11

## Activity 5 solution (2)

2(2 + jω )
→ 2e−2t cos(5t)u(t)
(2 + jω )2 + 52
4*5
2 2
→ 4e−2t sin(5t)u(t)
(2 + jω ) + 5

12
12

6
17-02-14

## Activity 6 Partial fraction expression method

Using the partial fraction expression method, calculate the
inverse CTFT of the following function:
5 ( jω ) + 30
X (ω ) =
( jω + 2)( jω + 5)( jω +10)

13
13

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 6 solution
5 ( jω ) + 30 k1 k k3
X (ω ) = = + 2 +
( jω + 2)( jω + 5)( jω +10) jω + 2 jω + 5 jω +10

## The partial fraction coefficients are given by:

5 ( jω ) + 30 5* (−2) + 30 5
k1 = ( jω + 2) = =
( jω + 2)( jω + 5)( jω +10) jω =−2
(−2 + 5)(−2 +10) 6
5 ( jω ) + 30 5* (−5) + 30 1
k2 = ( jω + 5) = =
( jω + 2)( jω + 5)( jω +10) jω =−5
(−5 + 2)(−5 +10) 3
5 ( jω ) + 30 5* (−10) + 30 1
k3 = ( jω +10) = =−
( jω + 2)( jω + 5)( jω +10) jω =−10
(−10 + 2)(−10 + 5) 2
14
14

7
17-02-14

## Activity 6 solution (2)

5 ( jω ) + 30
X (ω ) =
( jω + 2)( jω + 5)( jω +10)
5 1 1
= + −
6( jω + 2) 3( jω + 5) 2( jω +10)

## Using the CTFT pairs in Table 5.2, the function is calculated

as:
⎡5 1 1 ⎤
x(t) = ⎢ e−2t + e−5t − e−10t ⎥ u(t)
⎣6 3 2 ⎦

15

## Activity 7 CTFT of Real-valued functions

Consider a function g(t) whose CTFT is given by:

G (ω ) = 1+ 2πδ (ω − ω 0 )

16
16

8
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 7 solution
Substituting ω with –ω into G(ω), we have

## The complex conjugate of G(ω) is:

*
G * (ω ) = [1+ 2πδ (ω − ω 0 )] = 1+ 2πδ (ω − ω 0 )

Obviously G * (ω ) ≠ G(−ω )

17
17

## Activity 7 solution (2)

To verify,
g (t ) = F −1 [1+ 2πδ (−ω − ω 0 )] = F −1[1]+ 2π F −1 [δ (−ω − ω 0 )]

## From Table 5.2, we have:

F −1[1] → δ (t)
F −1 [ 2πδ (ω − ω 0 )] → e jω0t

18
18

9
17-02-14

## EECE 2602 -- Signals and Systems in Continuous Time

Activity 8
Determine the Fourier transform of the sine function cos(ω0t).

19
19

## EECE 2602 -- Signals and Systems in Continuous Time 20

Activity 8 Solution
Given
1
cos(ω 0 t) = ⎡⎣e jω0t + e− jω0t ⎤⎦
2
jω 0t CTFT
e ←⎯⎯→ 2πδ (ω − ω 0 )
e− jω0t ←⎯⎯
CTFT
→ 2πδ (ω + ω 0 )
Applying linear property:

1 1
F {cos(ω 0 t)} = F {e jω0t } + F {e− jω0t } = π [δ (ω − ω 0 ) + δ (ω + ω 0 )]
2 2

20

10